201 Association between undiagnosed sleep disorders and cardiovascular disease in healthy truck drivers. (24th April 2018) - Magnavita, Nicola; Bortkiewicz, Alicja; Durando, Paolo; Garbarino, Sergio
Abstract : Introduction: Sleep disorders (SD), including obstructive sleep apnea (OSA), sleep loss, and insomnia are highly prevalent and underdiagnosed conditions that have negative impacts on quality of life, mood, cognitive function, and cardiovascular disease (CVD). The aim of the study was to explore the prevalence and the relationship between SD and CVD in healthy truck drivers with undiagnosed and untreated sleep disorders. Methods: Trained medical staff offered a free medical examination to truck drivers parked in some of the major Italian trucking hubs. The study enrolled 949 truck drivers. The prevalence of SD and CVD was clinically assessed. Results: 177 truck drivers (18.7%) had CVD. Multivariate logistic regression showed that SD are significant predictors of CVD. Drivers with OSA had a more than three-fold increased risk of CVD (OR 3.41, 95% CI: 2.30 to 5.04). Insomniac drivers had an increased risk of CVD (OR 1.54 95% CI: 1.00 to 2.31). Age and obesity (body mass index, BMI) were also associated with increased odds for CVD. Sleep loss, and short sleep duration, were not independently associated with CVD in the multivariate model. Discussion: Evidence suggests that obstructive sleep apnea (OSA) is related to cardiovascular disease. Insomnia can also be associated with CVD, even if the association is less evident. Sleep is increasingly recognised as an important lifestyle contributor to health.